The Impact of Osteoporosis on 2-Year Outcomes in Patients Undergoing Long Cervical Fusion. Issue 1 (1st January 2023) - Diebo, Bassel G.; Scheer, Ryan; Rompala, Alexander; Veenema, Ryne J.; Shah, Neil V.; Beyer, George A.; Celiker, Pelin; Eldib, Hassan; Passfall, Lara; Krol, Oscar; Dubner, Michael G.; Lafage, Renaud; et al.
Abstract : Introduction: Osteoporosis affects nearly 200 million individuals worldwide. Given this notable disease burden, there have been increased efforts to investigate complications in patients with osteoporosis undergoing cervical fusion (CF). However, there are limited data regarding long-term outcomes in osteoporotic patients in the setting of ≥4-level cervical fusion. Methods: The New York State Statewide Planning and Research Cooperative System database was used to identify patients who underwent posterior or combined anterior-posterior ≥4-level CF for cervical radiculopathy or myelopathy from 2009 to 2011, with a minimum follow-up surveillance of 2 years. The following were compared between patients with and without osteoporosis: demographics, hospital-related parameters, medical/surgical complications, readmissions, and revisions. Binary multivariate stepwise logistic regression was used to identify independent predictors of outcomes. Results: A total of 2, 604 patients were included (osteoporosis: n = 136 (5.2%); nonosteoporosis: n = 2, 468). Patients with osteoporosis were older (66.9 ± 11.2 vs. 60.0 ± 11.4 years, P < 0.001), more often female (75.7% vs. 36.2%, P < 0.001), and White (80.0% vs. 65.3%, P = 0.007). Both cohorts had comparable comorbidity burdens (Charlson/Deyo: 1.1 ± 1.2 vs. 1.0 ± 1.3, P = 0.262), total hospital charges ($100, 953 ± 94, 933 vs. $91, 618 ± 78, 327, P = 0.181), and length of stay (9.7 ± 10.4 vs. 8.4 ± 9.6 days, P = 0.109). Patients with osteoporosis incurred higher rates of overall medical complication rates (41.9% vs. 29.4%, P = 0.002) and individual surgical complications, such as nonunion (2.9% vs. 0.7%, P = 0.006). Osteoporosis was associated with medical complications (OR = 1.57, P = 0.021), surgical complications (OR = 1.52, P = 0.030), and readmissions (OR = 1.86, P = 0.003) at 2 years. Discussion: Among patients who underwent multilevel cervical fusion, those with osteoporosis had higher risk of adverse postoperative outcomes at two years. These data indicate that preoperative screening and management of osteoporosis may be important for optimizing long-term outcomes in patients who require multilevel CF. Data availability and trial registration numbers: The data used in this study are available for public use at https://www.health.ny.gov/statistics/sparcs/ .